Experiential Meaning in Spoken Speech in Javanese: A Study of Transitivity Based on Systemic Functional Linguistics - Wulan, Sri Hertanti; Mulyani, Siti; Herman, Herman (Journal of Language and Literature Studies, 2026)
Spoken Javanese is a form of communication rich in cultural meaning, as it represents speakers’ social relationships, attitudes, and experiences in everyday interactions. In this context, the transitivity system in Systemic Functional Linguistics (SFL) is relevant for examining the representation of experiential meaning through language. This study aims to identify the types of processes in the transitivity system found in spoken Javanese utterances, analyze the distribution and dominance of the processes that occur, and interpret the tendencies in the representation of speakers’ experiences within the Javanese sociocultural context. This research employs a qualitative descriptive approach. The data consist of 134 spoken Javanese utterances obtained through observation and interviews in natural interactions. The analysis was conducted through data reduction, clause identification, process type classification, and meaning interpretation based on the sociocultural context. Since a single utterance may contain more than one clause, the number of processes identified exceeds the number of utterances. The findings reveal the occurrence of mental processes in 63 clauses, behavioral processes in 38 clauses, material processes in 17 clauses, relational processes in 13 clauses, verbal processes in 9 clauses, and existential processes in 6 clauses. Mental processes are the most dominant, particularly in the desiderative and cognitive subcategories, which represent speakers’ desires, considerations, and inner attitudes. These findings indicate that spoken Javanese tends to represent internal experiences and interpersonal negotiation more frequently than material actions. This study confirms that the transitivity system functions not only as a grammatical structure but also as a representation of experience that reflects the sociocultural orientation of its speakers.